The frequency of sensitization to inhalatory allergens and concomitant rhinitis in asthmatic patients - Zvezdin Biljana; Milutinov Senka; Tanasković Ivana; Kojičić Marija; Kolarov Violeta; Hromiš Sanja; Ilić Miroslav (Vojnosanitetski Pregled)
Background/Aim. Asthma is one of the most common chronic pulmonary diseases. The number of asthmatics has been continuously increasing all over the world. Depending on its causing agent, asthma is classified as allergic and nonallergic. Asthma is often associated with other allergic diseases, and it is most commonly preceded by the symptoms of rhinitis. The aim of this study was to establish the type and frequency of allergic sensitization to inhalatory allergens, frequency of concomitant rhinitis, gender and age-related distribution of asthma, and the presence of some risk factors in patients with diagnosed asthma. Methods. This retrospective and partially prospective analysis included 733 patients with asthma diagnosed in the Institute for Pulmonary Diseases of Vojvodina, Sremska Kamenica over the period January, 2004-December, 2008. The obtained date were statistically processed. Results. Females were significantly more often affected by asthma (p < 0.05), most frequently at 20-29 years of age. A hereditary predisposition to the diseases in terms of atopy was registered in 34.9% of the examined subjects. Most patients had allergic asthma (79.5%). Sensitization to internal and external inhalatory allergens was verified in 77.5% and 67.6% of the patients respectively, and combined hypersensitivity to both allergen types in 48.8% of the patients. Rhinitis was registered in 63.9% and 28% of the patients with allergic and nonallergic asthma, respectively. Rhinitis symptoms preceded the occurrence of asthma in 60% of the patients, with the precedence of rhinitis ranging from 1 to 27 years. A high correlation between rhinitis and asthma was established for the disease of both allergic (r = 0.92) and nonallergic (r = 0.88) etiology. Conclusion. The majority of the patients have allergic asthma, and they are females at 20-29 years of age. Senstization to internal allergens is most common, and then to external ones. Rhinitis is the most common concomitant disease, usually preceding the occurrence of asthmatic symptoms.